Duck Days. - Leach, Sara (Pajama Press, 2020)
The third title in the collection that began with USBBY Outstanding International Book Slug Days. Lauren, a third-grade student who has Autism Spectrum Disorder, takes on the challenges of sharing her best friend and persevering when a classmate mocks her bicycle's training wheels.